Novel poly(spirobisindane-arylpiperidinium) copolymer ionomer, anion exchange membrane and its manufacturing method
Patent Information
- Application Number
- JP2024543398
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-24
- Filing Date
- 2023-01-19
- Publication Date
- 2025-02-20
AI Technical Summary
【0028】 本発明に係る新規ポリ(スピロビスインダン-アリールピペリジニウム)共重合体イオノマーは、化学的安定性及び機械的物性に優れ、イオン伝導度が高く、気体透過能が向上し、且つ物質伝達抵抗が減少する。
Smart Images

Figure 2025505066000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel poly(spirobisindane-arylpiperidinium) copolymer ionomer, anion exchange membrane and a method for producing the same. More specifically, the present invention relates to a technology for synthesizing a poly(spirobisindane-arylpiperidinium) copolymer having no aryl ether bond in the polymer backbone, containing a spirobisindane group in the repeating unit while a piperidinium group is introduced, producing an anion exchange membrane therefrom, and applying the membrane to alkaline fuel cells, water electrolysis devices, carbon dioxide reduction, metal-air batteries, etc. [Background technology]
[0002] To date, polymer electrolyte membrane fuel cells (PEMFCs) have been the subject of much research due to their relatively high current density and environmental friendliness. In particular, perfluorinated carbon-based proton exchange membranes, such as Nafion, are the most commonly used polymer electrolyte membranes. However, Nafion membranes require the use of platinum-based precious metal catalysts due to their low oxygen reduction reaction (ORR), making them very expensive and low in glass transition temperature. For this reason, active research is being conducted to replace Nafion, including the development of aromatic hydrocarbon-based polymer electrolyte membranes.
[0003] Among these studies, alkaline membrane fuel cells (AMFCs) using anion exchange membranes and water electrolysis are known to have excellent performance and significantly higher cost competitiveness because they can use inexpensive non-precious metals such as nickel and manganese as electrode catalysts instead of platinum, and research is ongoing. However, there is a problem of low long-term stability due to the decomposition behavior of hydroxyl radicals and ions during operation, and research is currently needed to improve the durability of alkaline membrane fuel cells.
[0004] A synthesis method is known in which benzyltrimethylammonium groups are introduced into aryl ether aromatic polymer structures such as polysulfone (PSF), polyphenyl ether (PPO) or polyether ether ketone (PEEK) as anion exchange membranes for alkaline membrane fuel cells, and the formation of repeating units with aryl ether (CO) bonds along the polymer backbone has the effect of improving the solubility of the polymer. However, the aryl ether bonds in the polymer backbone cause hydroxyl radical decomposition of the electrolyte membrane during fuel cell operation, resulting in a problem of reduced long-term stability. Therefore, preventing the decomposition of the polymer backbone has become a problem to be solved in order to improve the durability of alkaline membrane fuel cells.
[0005] In addition, because conventional anion exchange membranes have limited chemical stability (less than 500 hours in 1M NaOH solution at 80°C) and mechanical properties (tensile strength less than 30 MPa), fuel cells using them have low power density (0.1 to 0.5 W cm -2 ) and has low durability. In addition, when used as a binder, the high phenyl structure has an adsorption effect, which limits the formation of three-phase boundaries, resulting in reduced fuel efficiency.
[0006] In addition, the water permeability of an anion exchange polymer is very important in the water management of an anion exchange membrane fuel cell. The positive electrode may be flooded with water due to electrochemical water generation, while the negative electrode is prone to drying due to water consumption. Therefore, polymers with high water content and expansion rate increase mass transfer resistance and inhibit electrochemical stability, greatly affecting durability.
[0007] Meanwhile, a poly(spirobisindane-arylpiperidinium) copolymer ionomer having no aryl ether bond in the polymer backbone, containing a spirobisindane group in the repeating unit, and having a piperidinium group introduced therein has not been synthesized, and no specific technology has been known for applying it to alkaline fuel cell membranes and binders or in the field of water electrolysis.
[0008] Therefore, the present inventors have conducted extensive research to expand the application field of aromatic polymer ion exchange membranes with excellent thermal and chemical stability and mechanical properties, and have attempted to solve the problems of conventional anion exchange polymers, such as low ionic conductivity, water content, mechanical properties, power density, durability, etc., by incorporating a spirobisindane group and a piperidinium group into the repeating unit of the anion exchange polymer. That is, the inventors have synthesized a poly(spirobisindane-arylpiperidinium) copolymer ionomer having no aryl ether bond in the polymer skeleton, containing a spirobisindane group, and having a piperidinium group introduced therein, and have produced an anion exchange membrane from the polymer, and have discovered that the membrane can be applied to alkaline fuel cell membranes and binders, water electrolysis devices, carbon dioxide reduction devices, metal-air batteries, etc., and have completed the present invention. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Korean Patent Publication No. 10-2018-0121961 [Patent Document 2] International Patent Publication WO2019 / 068051 [Patent Document 3] Japanese Patent Publication No. 2020-536165 [Patent Document 4] U.S. Patent Publication US2019 / 0036143 Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention has been devised in view of the above problems, and a first object of the present invention is to provide a novel poly(spirobisindane-arylpiperidinium) copolymer ionomer having excellent chemical stability and mechanical properties, high ionic conductivity, improved gas permeability, and reduced mass transfer resistance, and a method for producing the same.
[0011] The second object of the present invention is to prepare an anion exchange membrane and a composite membrane thereof from the novel poly(spirobisindane-arylpiperidinium) copolymer ionomer and apply them to membranes and binders for alkaline fuel cells, water electrolysis devices, carbon dioxide reduction devices, metal-air batteries, etc., which have excellent chemical stability, mechanical properties, durability, and water management capabilities. [Means for solving the problem]
[0012] In order to achieve the above object, the present invention provides a poly(spirobisindane-arylpiperidinium) copolymer ionomer having a repeating unit represented by the following formula 1.
[0013] [ka]
[0014] In the above formula 1, aryl is any one selected from the compounds represented by the structural formula of the following formula 2.
[0015] [ka]
[0016] m and n are the mole fractions (%) in the repeating unit of the copolymer ionomer, where m>0, n>0, and m+n=100.
[0017] The present invention also provides a method for producing a poly(spirobisindane-arylpiperidinium) copolymer ionomer, comprising: (I) dissolving a monomer selected from 6,6'-dimethoxy-3,3,3',3'-tetramethyl-2,2',3,3'-tetrahydro-1,1'-spirobisindane, 1-methyl-4-piperidone, and a compound represented by the following structural formula 3 in an organic solvent to form a solution; (II) gradually adding a strong acid catalyst to the solution, stirring and reacting to obtain a viscous solution; (III) precipitating, washing and drying the viscous solution to obtain a solid polymer; (IV) adding and reacting K2CO3 and an excess amount of halomethane to a polymer solution obtained by dissolving the solid polymer in an organic solvent to form a quaternary piperidinium salt; and (V) precipitating, washing and drying the polymer solution.
[0018] [ka]
[0019] The present invention also provides an anion exchange membrane comprising the poly(spirobisindane-arylpiperidinium) copolymer ionomer.
[0020] The present invention also provides an anion exchange composite membrane comprising: a porous polymer support; and the anion exchange membrane impregnated in the porous polymer support.
[0021] The present invention also provides a method for producing an anion exchange membrane, comprising: (a) dissolving the poly(spirobisindane-arylpiperidinium) copolymer ionomer in an organic solvent to form a polymer solution; (b) casting the polymer solution on a glass plate and drying it to obtain a membrane; and (c) treating the obtained membrane with 1M NaHCO3 or 1M NaOH, washing with ultrapure water several times, and drying.
[0022] The present invention also provides a method for producing an anion exchange composite membrane, comprising: (i) preparing a porous polymer support; (ii) adding a co-solvent to a polymer solution in which the poly(spirobisindane-arylpiperidinium) copolymer ionomer is dissolved in an organic solvent to obtain an ionomer solution; and (iii) casting the ionomer solution on the porous polymer support, impregnating the porous polymer support, and drying the same.
[0023] The present invention also provides a binder for alkaline fuel cells, which comprises the poly(spirobisindane-arylpiperidinium) copolymer ionomer.
[0024] The present invention also provides an alkaline fuel cell comprising the anion exchange membrane or composite anion exchange membrane.
[0025] The present invention also provides a water electrolysis device comprising the anion exchange membrane or the composite anion exchange membrane.
[0026] The present invention also provides a carbon dioxide reduction device comprising the anion exchange membrane or the anion exchange composite membrane.
[0027] The present invention also provides a metal-air battery comprising the anion exchange membrane or the composite anion exchange membrane. Effect of the Invention
[0028] The novel poly(spirobisindane-arylpiperidinium) copolymer ionomer according to the present invention has excellent chemical stability and mechanical properties, high ionic conductivity, improved gas permeability, and reduced mass transfer resistance.
[0029] In addition, the anion exchange membrane and its composite membrane prepared from the poly(spirobisindane-arylpiperidinium) copolymer ionomer have excellent chemical stability, mechanical properties, durability, and water management ability, and can be applied to membranes and binders for alkaline fuel cells, water electrolysis devices, carbon dioxide reduction devices, metal-air batteries, etc. [Brief description of the drawings]
[0030] [Figure 1] 1 is a partial nuclear magnetic resonance ( 1 H NMR) spectrum of PSTM and PSTP prepared according to Example 1 of the present invention. [Diagram 2] 1 shows the nuclear magnetic resonance ( 1 H NMR) spectra of some of the PSBM and PSBP prepared according to Example 2 of the present invention. [Diagram 3] 1 shows nuclear magnetic resonance ( 1 H NMR) spectra of PSDM-20 and PSDP-20 prepared according to Example 3 of the present invention. [Figure 4] 1 is a graph showing the dimensional stability of the anion exchange membranes produced in Examples 1 to 3 of the present invention. [Diagram 5] 1 is a graph showing some of the mechanical properties of the anion exchange membranes produced in Examples 1 to 3 of the present invention. [Figure 6] 1 is a graph showing the ionic conductivity of some of the anion exchange membranes produced according to Examples 1 and 2 of the present invention. [Figure 7] 1 is an image showing the ion channel size and the degree of phase separation of the anion exchange membranes produced in Examples 1 to 3 of the present invention. [Figure 8] 1 is a graph showing (a) hydrogen permeability and (b) water permeability of the anion exchange membrane (PSTP-20) produced in Example 1 of the present invention, the anion exchange membranes (PFTP, PFBP) produced in Comparative Examples 1 and 2, and a conventionally commercialized anion exchange membrane (FAA-3-50) as a control. [Figure 9] 2 is a graph showing the fuel cell performance of a portion of the anion exchange membrane produced according to Example 1 of the present invention. [Figure 10] 1 is a graph showing the CO2 adsorption / desorption behavior of the anion exchange membrane (PSTP-20) prepared in Example 1 of the present invention, the anion exchange membranes (PFTP, PFBP) prepared in Comparative Examples 1 and 2, and a conventionally commercialized anion exchange membrane (FAAM) as a control. [Figure 11]1 is a graph showing the water diffusivity (H2O diffusivity) of the anion exchange membrane (PSBP-10) prepared in Example 2 of the present invention, the anion exchange membranes (PFTP, PFBP) prepared in Comparative Examples 1 and 2, and a conventional commercial anion exchange membrane (FAA-3-50) as a control. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] Hereinafter, the novel poly(spirobisindane-arylpiperidinium) copolymer ionomer, anion exchange membrane, and production method thereof according to the present invention will be described in detail.
[0032] The present invention provides a poly(spirobisindane-arylpiperidinium) copolymer ionomer having a repeating unit represented by the following formula 4.
[0033] [ka]
[0034] In the above formula 4, aryl is any one selected from the compounds represented by the structural formula of the following formula 5.
[0035] [ka]
[0036] m and n are the mole fractions (%) in the repeating unit of the copolymer ionomer, where m>0, n>0, and m+n=100.
[0037] As shown in the above formula 4, the present invention produces a novel poly(spirobisindane-arylpiperidinium) copolymer ionomer, which is basically composed of a stable main chain without aryl ether bonds and a piperidinium group that exhibits high chemical stability, and can greatly improve film-forming ability and mechanical properties.
[0038] In particular, the introduction of spirobisindane groups improves mass transfer ability and suppresses the expansion rate, thereby improving dimensional stability. The bulky structure of the spirobisindane groups prevents the main chain from folding, providing excellent permeability, so the poly(spirobisindane-arylpiperidinium) copolymer ionomer of the present invention has high gas permeability and reduced mass transfer resistance.
[0039] In addition, the ratio of spirobisindane groups in the repeating unit can be adjusted to adjust the ion exchange capacity (IEC), morphology, etc. When the ratio of spirobisindane groups is high, gas permeability is improved and it can be used as a binder, and when the ratio of spirobisindane groups is low, it can be used as an anion exchange membrane due to excellent mechanical properties and low expansion coefficient.
[0040] In addition, the poly(spirobisindane-arylpiperidinium) copolymer ionomer of the present invention, which contains a robust spirobisindane group, exhibits excellent ionic conductivity and dimensional stability at the same time. Moreover, the phenyl adsorption is reduced, which is favorable for the formation of a three-phase interface, and therefore, the ionomer exhibits excellent electrochemical properties.
[0041] In addition, since the spirobisindane monomer is highly reactive, it is possible to synthesize a polymer having a high molecular weight. The poly(spirobisindane-arylpiperidinium) copolymer ionomer of the present invention containing this monomer exhibits high solubility in organic solvents such as dimethyl sulfoxide (DMSO), making it possible to perform solution casting. This is also advantageous in producing reinforced composite membranes, and may lead to mass production.
[0042] The present invention also provides a method for producing a poly(spirobisindane-arylpiperidinium) copolymer ionomer, comprising: (I) dissolving a monomer selected from 6,6'-dimethoxy-3,3,3',3'-tetramethyl-2,2',3,3'-tetrahydro-1,1'-spirobisindane, 1-methyl-4-piperidone, and a compound represented by the following structural formula in an organic solvent to form a solution; (II) gradually adding a strong acid catalyst to the solution, stirring and reacting to obtain a viscous solution; (III) precipitating, washing and drying the viscous solution to obtain a solid polymer; (IV) adding and reacting K2CO3 and an excess amount of halomethane to a polymer solution obtained by dissolving the solid polymer in an organic solvent to form a quaternary piperidinium salt; and (V) precipitating, washing and drying the polymer solution.
[0043] [ka]
[0044] First, in order to prepare poly(spirobisindane-arylpiperidinium) copolymer, a monomer selected from 6,6'-dimethoxy-3,3,3',3'-tetramethyl-2,2',3,3'-tetrahydro-1,1'-spirobisindane, 1-methyl-4-piperidone, and a compound represented by the structural formula of Chemical Formula 6 is reacted. At this time, the molar fraction of the spirobisindane monomer can be adjusted in various ways to be used in the final binder or anion exchange membrane, and more preferably, the molar fraction of the spirobisindane group in the copolymer repeating unit is adjusted to 10 to 70%.
[0045] Next, the poly(spirobisindane-arylpiperidinium) copolymer having various aryl segments consisting of the compounds defined by the above structural formula, including the spirobisindane segment, is reacted with halomethane to produce the desired poly(spirobisindane-arylpiperidinium) copolymer ionomer in which a quaternary piperidinium salt is formed.
[0046] Here, the organic solvent in step (I) may be at least one halogen-based solvent selected from the group consisting of dichloromethane, chloroform, dichloroethane, dibromomethane, and tetrachloroethane, and preferably dichloromethane.
[0047] The strong acid catalyst in step (II) may be trifluoroacetic acid, trifluoromethanesulfonic acid, pentafluoroethanesulfonic acid, heptafluoro-1-propanesulfonic acid, perfluoropropionic acid, heptafluorobutyric acid, or a mixture thereof, and preferably, a mixture of trifluoroacetic acid / trifluoromethanesulfonic acid is used.
[0048] Additionally, the organic solvent in step (IV) may be N-methylpyrrolidone, dimethylacetamide, dimethylsulfoxide, or dimethylformamide.
[0049] In step (IV), the polymer is reacted with a halomethane to form a quaternary piperidinium salt, the halomethane may be fluoromethane, chloromethane, bromomethane or iodomethane, and preferably iodomethane is used.
[0050] The present invention also provides an anion exchange membrane comprising the poly(spirobisindane-arylpiperidinium) copolymer ionomer.
[0051] The present invention also provides an anion exchange composite membrane comprising: a porous polymer support; and the anion exchange membrane impregnated in the porous polymer support.
[0052] The porous polymer support may be selected from the group consisting of polyethylene, polypropylene, polytetrafluoroethylene, polyvinylidene fluoride, polyhexafluoropropylene, and polyperfluoroalkylvinyl ether, but is not limited thereto.
[0053] Furthermore, the porous polymer support is more preferably one having a pore size of 0.01 μm to 0.5 μm and a porosity of 50% to 90%, which allows for stable impregnation with the poly(spirobisindane-arylpiperidinium) copolymer ionomer solution.
[0054] In addition, since most of the porous polymer supports are hydrophobic, the surface of the porous polymer support may be fluorinated or hydrophilized in order to improve the affinity between the porous polymer support and the poly(spirobisindane-arylpiperidinium) copolymer and to stably impregnate the polymer ionomer solution to form a defect-free anion exchange membrane.
[0055] Specifically, the fluorination treatment is carried out by immersing a porous polymer support in an ethanol solution, ultrasonically dispersing the support at -10°C to 25°C, and then removing the porous polymer support and drying it at room temperature. The dried porous polymer support is then placed in a vacuum chamber, and the inside of the chamber is purged with nitrogen gas to create an inert atmosphere. Thereafter, fluorine gas (500±15 ppm F2 / N2 at atmospheric pressure) is supplied to the vacuum chamber at a rate of 1 L / min, and the surface is directly fluorinated at room temperature for 5 to 60 minutes to obtain a fluorinated porous polymer support, and residual fluorine gas is removed using nitrogen gas in a scrubber containing activated carbon.
[0056] On the other hand, as a hydrophilization treatment, a hydrophilic alkyl alcohol having 1 to 3 carbon atoms may be applied to the surface of the porous polymer support, or the support may be coated with a hydrophilic polymer such as dopamine or polyvinyl alcohol.
[0057] The present invention also provides a method for producing an anion exchange membrane, comprising: (a) dissolving the poly(spirobisindane-arylpiperidinium) copolymer ionomer in an organic solvent to form a polymer solution; (b) casting the polymer solution on a glass plate and drying it to obtain a membrane; and (c) treating the obtained membrane with 1M NaHCO3 or 1M NaOH, washing with ultrapure water several times, and drying.
[0058] Here, the organic solvent in step (a) may be N-methylpyrrolidone, dimethylacetamide, dimethylsulfoxide, or dimethylformamide.
[0059] The concentration of the polymer solution is preferably 2 to 30% by weight, and more preferably 3.0 to 5.0% by weight. If the concentration of the polymer solution is less than 2% by weight, the film-forming ability may decrease, whereas if it exceeds 30% by weight, the viscosity may become excessively high, and the physical properties of the film may decrease after film formation.
[0060] In addition, the drying in step (b) is preferably carried out by gradually removing the organic solvent in an oven at 80 to 90° C. for 24 hours, and then heating in a vacuum oven at 120 to 150° C. for 12 hours to completely remove the organic solvent.
[0061] Next, the poly(spirobisindane-arylpiperidinium) copolymer ionomer membrane obtained by steps (a) and (b) was treated with 1M NaHCO3 or 1M NaOH to obtain the halide form (I - form, etc.) to HCO3 - Or OH - It is possible to produce an anion exchange membrane in which the anion exchange membrane has been converted into the above form.
[0062] The present invention also provides a method for producing an anion exchange composite membrane, comprising: (i) preparing a porous polymer support; (ii) adding a co-solvent to a polymer solution in which the poly(spirobisindane-arylpiperidinium) copolymer ionomer is dissolved in an organic solvent to obtain an ionomer solution; and (iii) casting the ionomer solution on the porous polymer support, impregnating the ionomer solution, and drying the same.
[0063] The porous polymer support in step (i) may have a surface that has been fluorinated or hydrophilized, and the fluorination or hydrophilization may be performed in the same manner as described above.
[0064] The organic solvent in step (ii) may be N-methylpyrrolidone, dimethylacetamide, dimethylsulfoxide, or dimethylformamide, and preferably dimethylsulfoxide.
[0065] In addition, in the present invention, unlike the conventional method, in order to improve the degree of impregnation of the ionomer polymer solution impregnated into the porous polymer support during the composite membrane manufacturing process, a co-solvent is added to a polymer solution obtained by dissolving the poly(spirobisindane-arylpiperidinium) copolymer ionomer in an organic solvent to obtain an ionomer polymer solution. This is the key technical feature of the anion exchange composite membrane manufacturing method according to the present invention, and has the advantages that a composite membrane can be obtained by a simple method of casting a polymer solution on a porous polymer support, the manufacturing process is simple, it can be manufactured as a highly concentrated solution, and it is mass-produced.
[0066] In the process of selecting the co-solvent, the contact angles of various organic solvents are measured to calculate the interfacial tension with the porous polymer support. Accordingly, methanol, ethanol, or isopropyl alcohol can be used as the co-solvent, and ethanol is particularly preferred.
[0067] In this case, the content of the co-solvent added in the step (II) is preferably 2 to 25% by weight based on the polymer solution. If the content of the co-solvent added is less than 2% by weight based on the polymer solution, it is difficult to impregnate the ionomer polymer solution into the porous polymer support, and if the content exceeds 25% by weight, it is difficult to obtain a high-concentration polymer solution.
[0068] The present invention also provides a binder for alkaline fuel cells, which comprises the poly(spirobisindane-arylpiperidinium) copolymer ionomer.
[0069] The present invention also provides an alkaline fuel cell comprising the anion exchange membrane or composite anion exchange membrane.
[0070] The present invention also provides a water electrolysis device comprising the anion exchange membrane or the composite anion exchange membrane.
[0071] The present invention also provides a carbon dioxide reduction device comprising the anion exchange membrane or the anion exchange composite membrane.
[0072] The present invention also provides a metal-air battery comprising the anion exchange membrane or the composite anion exchange membrane.
[0073] Hereinafter, examples and comparative examples according to the present invention will be specifically described with reference to the accompanying drawings.
[0074] [Example 1] Preparation of poly(spirobisindane-arylpiperidinium) copolymer ionomer (PSTP).
[0075] As monomers, 6,6'-dimethoxy-3,3,3',3'-tetramethyl-2,2',3,3'-tetrahydro-1,1'-spirobisindane (1.009g, 3mmol), terphenyl (6.218g, 27mmol), and 1-methyl-4-piperidone (4.073g, 36mmol) were added to a 100mL reactor, and dichloromethane (24mL) was added and stirred to dissolve the monomers to form a solution. The temperature of the solution was cooled to 1°C, and then a mixture of trifluoroacetic acid (3.6mL) and trifluoromethanesulfonic acid (18mL) was gradually added to the solution, and the mixture was stirred and reacted for 8 hours to obtain a viscous solution. The viscous solution was poured into 500 mL of distilled water, washed several times with deionized water, and dried in an oven at 80 °C for 24 h to prepare a solid poly(spirobisindane-co-terphenyl-N-methylpiperidine) copolymer (yield 94.8%), which was named PSTM-10.
[0076] Next, the prepared PSTM-10 (10g, 20mmol) was dissolved in dimethylsulfoxide (100mL) to obtain a polymer solution, and then K2CO3 (6.9g, 50mmol) and iodomethane (8.46g, 60mmol) were added to the polymer solution and reacted at room temperature in a dark room for 24 hours to form a quaternary piperidinium salt. Next, the polymer solution was precipitated in 500mL of ethyl acetate, filtered, washed several times with deionized water, and dried in a vacuum oven at 80°C for 24 hours to prepare a solid poly(spirobisindane-co-terphenyl N,N-dimethylpiperidinium) copolymer ionomer (yield 92%), which was named PSTP-10 (the mole fraction of spirobisindane groups in the repeating unit is 10%).
[0077] In addition, poly(spirobisindane-co-terphenyl N-methylpiperidine) copolymers having a molar fraction of spirobisindane group in the repeating unit of 20%, 40% and 70% were synthesized in the same manner as above except that the content of 6,6'-dimethoxy-3,3,3',3'-tetramethyl-2,2',3,3'-tetrahydro-1,1'-spirobisindane reactant as a monomer was changed to different amounts (PSTM-20, PSTM-40, PSTM-70). Poly(spirobisindane-co-terphenyl N,N-dimethylpiperidinium) copolymer ionomers were also produced, and named PSTP-20, PSTP-40 and PSTP-70, respectively.
[0078] [Example 2] Preparation of poly(spirobisindane-arylpiperidinium) copolymer ionomer (PSBP).
[0079] Poly(spirobisindane-co-biphenyl N-methylpiperidine) copolymers were synthesized in the same manner as in Example 1, except that biphenyl was used instead of terphenyl as the monomer (PSBM-10, PSBM-20, PSBM-40, PSBM-70), and then poly(spirobisindane-co-biphenyl N,N-dimethylpiperidinium) copolymer ionomers were produced and named PSBP-10, PSBP-20, PSBP-40, and PSBP-70, respectively.
[0080] [Example 3] Preparation of poly(spirobisindane-arylpiperidinium) copolymer ionomer (PSDP).
[0081] Poly(spirobisindane-co-diphenylethane N-methylpiperidine) copolymers were synthesized in the same manner as in Example 1, except that diphenylethane was used instead of terphenyl as the monomer (PSDM-10, PSDM-20, PSDM-40, PSDM-70), and then poly(spirobisindane-co-diphenylethane N,N-dimethylpiperidinium) copolymer ionomers were produced and named PSDP-10, PSDP-20, PSDP-40, and PSDP-70, respectively.
[0082] [Example 4] Preparation of anion exchange membrane from poly(spirobisindane-arylpiperidinium) copolymer ionomer.
[0083] The PSTP, PSBP and PSDP series (1.7 g each) prepared in Examples 1 to 3 above were dissolved in dimethyl sulfoxide to form a polymer solution with a concentration of 4 wt%. The polymer solution was then filtered through a 0.45 μm PTFE filter, and the transparent solution was cast onto a 21 cm x 24 cm glass plate. The casting solution was dried in an oven at 90°C for 24 hours to gradually remove the solvent, and then heated in a vacuum oven at 140°C for 12 hours to completely remove the solvent, thereby obtaining the PSTP membrane, PSBP membrane and PSDP membrane series (I - morphology, thickness 25±5 μm) was obtained.
[0084] The obtained I - The PSTP, PSBP, and PSDP membranes were immersed in 1M NaHCO3 or 1M NaOH aqueous solution (room temperature, 24 hours), respectively, and the HCO3 - Or OH - The resulting mixture was washed several times with ultrapure water and dried to prepare an anion exchange membrane.
[0085] [Example 5] Preparation of anion exchange composite membrane.
[0086] A porous polyethylene support (PE) was prepared (purchased from W-Scope, thickness 10 μm or 20 μm). Ethanol was added as a co-solvent to a 27 wt% polymer solution obtained by dissolving PSTP-10 obtained in Example 1 above in dimethyl sulfoxide, to obtain an ionomer solution with a concentration of 25 wt%. The ionomer solution was cast onto the porous polyethylene support, and then dried in an oven at 100° C. for 10 minutes to gradually remove the solvent, and then further dried in a vacuum oven at 90° C. for 12 hours to completely remove the solvent, thereby producing an anion exchange composite membrane (PSTP-10@PE).
[0087] [Comparative Example 1] Production of an anion exchange membrane (PFTP) containing no spirobisindane groups.
[0088] A poly(fluorene-co-terphenyl N,N-dimethylpiperidinium) copolymer ionomer was prepared in the same manner as in Example 1, except that 9,9'-dimethylfluorene was used instead of 6,6'-dimethoxy-3,3,3',3'-tetramethyl-2,2',3,3'-tetrahydro-1,1'-spirobisindane as a monomer, and an anion exchange membrane (PFTP) was prepared therefrom in the same manner as in Example 4.
[0089] [Comparative Example 2] Preparation of an anion exchange membrane (PFBP) not containing spirobisindane groups.
[0090] A poly(fluorene-co-biphenyl N,N-dimethylpiperidinium) copolymer ionomer was prepared in the same manner as in Example 1, except that 9,9'-dimethylfluorene and biphenyl were used instead of 6,6'-dimethoxy-3,3,3',3'-tetramethyl-2,2',3,3'-tetrahydro-1,1'-spirobisindane and terphenyl, respectively, as monomers, and an anion exchange membrane (PFBP) was prepared therefrom in the same manner as in Example 4.
[0091] [Test example].
[0092] Test data such as mechanical properties, morphology, ion exchange performance, water content, expansion rate, ion conductivity and fuel cell performance of the anion exchange membranes manufactured according to the examples and comparative examples of the present invention were measured and evaluated according to the method described in the prior application published in Japanese Patent No. 10-2021-0071810 by the inventors of the present invention.
[0093] First, FIG. 1 shows the nuclear magnetic resonance (NMR) spectra of part of PSTM and PSTP prepared according to Example 1 of the present invention. 1 1 H NMR) spectrum, and FIG. 2 shows the nuclear magnetic resonance ( 1 1 H NMR) spectrum, and FIG. 3 shows the nuclear magnetic resonance ( 1 The 1 H NMR) spectra are shown. All of the synthesized structures are of high purity, and their respective nuclear magnetic resonance ( 1 As seen in the 1 H NMR spectrum, the characteristic peaks were clearly observed, confirming that the desired poly(spirobisindane-arylpiperidinium) copolymer ionomer had been synthesized.
[0094] FIG. 4 also shows the dimensional stability of the anion exchange membranes produced in Examples 1 to 3 of the present invention, and shows that as the ratio of robust spirobisindan groups increases, the expansion rate and water content decrease, and the dimensional stability improves.
[0095] FIG. 5 shows some of the mechanical properties of the anion exchange membranes prepared in Examples 1 to 3 of the present invention. The physical properties of the anion exchange membranes vary greatly depending on the form of the aryl structure contained in the repeating unit. When terphenyl is contained, the membranes exhibit excellent film-forming ability and mechanical properties and can be used as anion exchange membranes. When diphenylethane and biphenyl are introduced, the membranes can be used as binders due to their high ion exchange ability and water permeability.
[0096] FIG. 6 shows the ion conductivity of some of the anion exchange membranes produced in Examples 1 and 2 of the present invention. The PSTP used as the anion exchange membrane has an ion conductivity of 160 mS cm at 80° C. -1 On the other hand, the PSBP anion exchange membrane showed a tendency to decrease in conductivity at high temperatures (100% relative humidity condition) due to its relatively low dimensional stability.
[0097] In addition, Fig. 7 shows the ion channel size and the degree of phase separation of the anion exchange membranes produced in Examples 1 to 3 of the present invention, and the size of the ion channel and the hydrophilic region differed depending on whether the aryl structure introduced into the repeating unit was terphenyl, biphenyl, or diphenylethane. That is, the ion channel and the hydrophilic region appeared smallest in terphenyl, which has the lowest ion exchange capacity (IEC), and the ion channel and the hydrophilic region appeared largest in biphenyl, which has the highest ion exchange capacity. It is considered that as the ratio of spirobisindane groups increases, the ion exchange capacity decreases and the channel size and the hydrophilic region also decrease.
[0098] FIG. 8 shows (a) hydrogen permeability and (b) water permeability of the anion exchange membrane (PSTP-20) produced in Example 1 of the present invention, the anion exchange membranes (PFTP, PFBP) produced in Comparative Examples 1 and 2, and a conventionally commercialized anion exchange membrane (FAA-3-50) as a control (in FIG. 8, PFBP-0 means that no fluorene group is introduced into the repeating unit and a biphenyl group is included, PFBP-14 means that the molar fraction of the fluorene group in the repeating unit is 14% and that a biphenyl group is included, PFTP-0 means that no fluorene group is introduced into the repeating unit and a terphenyl group is included, and PFTP-13 means that the molar fraction of the fluorene group in the repeating unit is 13% and that a terphenyl group is included).
[0099] As shown in Fig. 8, the PSTP membrane exhibits higher hydrogen permeability than the PFBP binder prepared in Comparative Example 2. In addition, by increasing the ratio of spirobisindane groups with a bulky structure, the free volume increases, which is expected to further improve the permeability.
[0100] FIG. 9 shows the fuel cell performance of a part of the anion exchange membrane manufactured according to Example 1 of the present invention (performance evaluation conditions: anode / cathode relative humidity 75% / 100%, anode / cathode gas H2 / O2 1000 mL / min, cell 80°C, anode catalyst PtRu / C 0.39 mg cm). -2 , cathode catalyst Pt / C 0.26 mg cm -2 ), 2.25 W cm for H2-O2@80 °C, 1.3 bar using platinum group metal (PGM) catalyst -2 On the other hand, as the ratio of spirobisindan groups increases, the ion exchange capacity decreases, the conductivity decreases, and the gas permeability increases, which is thought to be the reason for the decrease in cell performance.
[0101] FIG. 10 shows the CO2 adsorption and desorption behavior of the anion exchange membrane (PSTP-20) produced in Example 1 of the present invention, the anion exchange membranes (PFTP, PFBP) produced in Comparative Examples 1 and 2, and a conventionally commercialized anion exchange membrane (FAAM) as a control.
[0102] The amount of CO2 molecules adsorbed and desorbed was shown to be higher in the order of PFTP≒PSTP>PDTP>PFTP(1atm). Ionomers with high CO2 adsorption and high permeability are suitable as binders in the field of carbon dioxide reduction. On the other hand, as the ratio of spirobisindane groups increases, the free volume increases due to the bulky structure, which is expected to increase the active sites and the amount of CO2 adsorption. This suggests that the ratio of spirobisindane groups can be adjusted to suit the application.
[0103] 11 shows the water sorption amount of the anion exchange membrane (PSBP-10) prepared in Example 2 of the present invention, the anion exchange membranes (PFTP, PFBP) prepared in Comparative Examples 1 and 2, and a conventional commercial anion exchange membrane (FAA-3-50) as a control. Table 1 below shows the ion exchange capacity (IEC) and water diffusivity of various known ionomers.
[0104] [Table 1]
[0105] 1. a, b, and c have the same meanings as those explained in Figure 8.
[0106] 2.d is a sample manufactured in the present inventor's prior patent application No. 10-2021-0168177.
[0107] 3.e is the following formula 7.
[0108] [ka]
[0109] 4.f is the following formula 8.
[0110] [ka]
[0111] 5.g is the following formula 9.
[0112] [ka]
[0113] The PSBP-10 of the present invention has a high water diffusion coefficient because of the increased free volume due to the spirobisindane group. On the other hand, when the ratio of the spirobisindane group is increased, the ion exchange capacity is decreased and the water adsorption amount is somewhat decreased, but the diffusion coefficient is increased.
[0114] Among the various ionomers shown in Table 1, the ionomer containing the spirobisindane group according to the present invention has a bulky structure that increases the free volume, resulting in a very high water diffusion coefficient, compared to the other ionomers.
Claims
1. A poly(spirobisindane-arylpiperidinium) copolymer ionomer having a repeating unit represented by the following formula 1. 【Chemistry 1】 (In the above formula 1, aryl is any one selected from the compounds represented by the following formula 2, 【Chemistry 2】 m and n are the mole fractions (%) in the repeating unit of the copolymer ionomer, where m>0, n>0, and m+n=100.
2. (I) dissolving a monomer selected from 6,6'-dimethoxy-3,3,3',3'-tetramethyl-2,2',3,3'-tetrahydro-1,1'-spirobisindane, 1-methyl-4-piperidone, and a compound represented by the following structural formula 3 in an organic solvent to form a solution; 【Chemistry 3】 (II) slowly adding a strong acid catalyst to the solution, stirring and reacting to obtain a viscous solution; (III) precipitating, washing and drying the viscous solution to obtain a solid polymer; (IV) The solid polymer is dissolved in an organic solvent to give a polymer solution. 2 CO 3 and adding and reacting with an excess of halomethane to form a quaternary piperidinium salt; and (V) precipitating, washing and drying the polymer solution.
3. The method for preparing poly(spirobisindane-arylpiperidinium) copolymer ionomer according to claim 2, wherein the organic solvent in step (I) is at least one selected from the group consisting of dichloromethane, chloroform, dichloroethane, dibromomethane and tetrachloroethane.
4. An anion exchange membrane comprising the poly(spirobisindane-arylpiperidinium) copolymer ionomer of claim 1.
5. A porous polymeric support; and 5. An anion exchange composite membrane comprising: the anion exchange membrane according to claim 4 impregnated in said porous polymer support.
6. (a) dissolving the poly(spirobisindane-arylpiperidinium) copolymer ionomer of claim 1 in an organic solvent to form a polymer solution; (b) casting the polymer solution onto a glass plate and drying to obtain a membrane; and (c) The obtained membrane was dissolved in 1M NaHCO 3 or a step of treating the anion exchange membrane with 1M NaOH, followed by washing the anion exchange membrane several times with ultrapure water and drying the same.
7. 7. The method for producing an anion exchange membrane according to claim 6, wherein the concentration of the polymer solution is 2 to 30% by weight.
8. 7. The method of claim 6, wherein the drying in step (b) comprises gradually removing the organic solvent in an oven at 80 to 90° C. for 24 hours, and then heating in a vacuum oven at 120 to 150° C. for 12 hours to completely remove the organic solvent.
9. (i) providing a porous polymeric support; (ii) adding a co-solvent to a polymer solution in which the poly(spirobisindane-arylpiperidinium) copolymer ionomer according to claim 1 is dissolved in an organic solvent to obtain an ionomer solution; and (iii) casting the ionomer solution onto a porous polymer support, impregnating and drying.
10. The method for preparing an anion exchange composite membrane according to claim 9, wherein the co-solvent in step (ii) is methanol, ethanol, or isopropyl alcohol.
11. A binder for alkaline fuel cells comprising the poly(spirobisindane-arylpiperidinium) copolymer ionomer of claim 1.
12. An alkaline fuel cell comprising the anion exchange membrane according to claim 4 or the anion exchange composite membrane according to claim 5.
13. A water electrolysis device comprising the anion exchange membrane according to claim 4 or the anion exchange composite membrane according to claim 5.
14. A carbon dioxide reduction device comprising the anion exchange membrane according to claim 4 or the anion exchange composite membrane according to claim 5.
15. A metal-air battery comprising the anion exchange membrane according to claim 4 or the anion exchange composite membrane according to claim 5.
Citation Information
Patent Citations
Poly(arylpiperidinium) polymers for use as hydroxide exchange membranes and hydroxide exchange ionomers
JP2019518809A
Poly(arylpiperidinium) polymers, including those with stable cationic pendant groups, for use as anion exchange membranes and ionomers
JP2020536165A
Wings of unmanned aerial vehicle with longitudinal strips to increase aerodynamic performance
KR1020210068375A
Poly(aryl piperidinium) polymers for use as hydroxide exchange membranes and ionomers
KR1020180121961A
Poly(aryl piperidinium) polymers for use as hydroxide exchange membranes and ionomers
US20190036143A1